Effects of tramadol on emergence agitation after general anesthesia for nasal surgery: A retrospective cohort study. Issue 10 (March 2019) - Lee, Seok-Jin; Choi, Seok Jun; In, Chi Bum; Sung, Tae-Yun
Abstract : Abstract: Emergence agitation (EA) is common after nasal surgery. Strong opioids and N -methyl-D-aspartate (NMDA) receptor antagonists prevent EA. Tramadol also acts as an opioid receptor agonist and an NMDA receptor antagonist, but few studies have evaluated the effects of tramadol on EA. This retrospective study investigated whether tramadol is effective for reducing EA in adult patients undergoing nasal surgery. Of 210 adult patients undergoing a nasal surgical procedure under general anesthesia, the medical records of 113 were analyzed retrospectively. The patients were divided into 2 groups: patients who received tramadol during the operation (tramadol group, n = 52) and patients who did not (control group, n = 61). The incidence of EA, recovery time, changes in hemodynamic parameters, postoperative pain scores, and adverse events were compared between the 2 groups. The incidence of EA was higher in the control group than in the tramadol group (50.8% [31/61] vs 26.9% [14/52]; odds ratio 2.805; 95% confidence interval, 1.3 to 6.2; P = .010). Changes in systolic blood pressure in the 2 groups were similar, whereas changes in heart rate during emergence differed depending on the group ( P = .020), although pairwise comparisons did not reveal any differences between the groups. Recovery time, postoperative pain scores, and adverse events were similar in the 2 groups. In adult patients undergoing nasal surgery, tramadol infusion decreases the incidence of EA after sevoflurane anesthesia without delaying recovery or increasing the number of adverse events.